STRATEGI SMALL GROUP DISCUSSION DALAM MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA PADA MATA PELAJARAN PAI DI SMP PLUS NUSANTARA - M Fachrezy Risdi; Zulfiana Herni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine how the Small Group Discussion (SGD) strategy can improve students’ communication skills in the Islamic Religious Education (PAI) subject at SMP Plus Nusantara. The Small Group Discussion (SGD) strategy was chosen because it is considered capable of encouraging active student participation in the learning process, honing speaking, listening, and effectively discussing skills within small groups. The research method usedwas qualitative with a case study approach. Data were collected through classroom observations, interviews with teachers and students, and documentation related to the implementation of Small Group Discussion (SGD) in the PAIclass. Data analysis was conducted using Miles and Huberman’s interactive analysis technique, which includes datareduction, data presentation, and conclusion verification. The results show that the implementation of the Small GroupDiscussion (SGD) strategy significantly improves students’ communication skills, as evidenced by the increased ability of students to express opinions, actively engage in discussions, and listen critically. Furthermore, students also demonstrated positive attitudes towards this method, making the learning process more engaging and interactive.However, some challenges were identified, such as differences in student ability levels and time management duringdiscussions, which need to be addressed for optimal strategy implementation. Thus, the Small Group Discussion(SGD) strategy is highly relevant and effective when used in PAI learning to enhance students’ communication skills. This study recommends that teachers pay attention to group management and material variation so that every student can participate optimally.